PENGARUHKUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA DISTRO HOUSE OF SMITH SEMARANG (Students' Journal of Economic and Management, 2016)
This study was done toanalyze the effects of product quality, price perception and promotion to purchase decisions in distroHouse Of SmithSemarang. The population in this study is that consumers who make purchases at the distroHouse Of SmithSemarang. Sampling method used in this study was "accidental sampling", which is a technique that determines the sample with particular consideration in accordance with the desired destination with the number of samples taken was 100 respondent.The data were analyzed using factor analysis to test the validity of the statement items, Cronbach alpha to test the reliability of the instrument, and regression analysis to test the effect of each independent variables were in the test on purchasing decisions. The results of this study indicate that the product quality, price perception and promotionhad positive and significant effect on purchasing decisions product in distroHouse Of SmithSemarang. The variable which had greatest effect on purchasing decisions was thepromotion and price perception, than followed by a variable product quality. Keyword: Product Quality, Perceived Price, Promotion and Purchase Decision